Hubungan Perilaku Personal Hygiene Dengan Kejadian Keputihan Pada Remaja Putri Di SMA Negeri 1 Godean - Listi Hari Muntasih; Fathiyatur Rohmah (CV. ITTC INDONESIA, 2025)
Vaginal discharge is one of the things that often occurs in adolescent girls.this disorder is the second problem after menstrual disorders.vaginal discharge is often not handled properly by adolescent girls because it is considered a normal thing,in fact continuous vaginal discharge can be an indication of the presence of certain diseases, This often overlooked reproductive health problem can result in fatal consequences if not treated early or properly.can cause infertility and ectopic pregnancy (pregnancy outside the womb), The initial symptoms of uterine cancer usually start with vaginal discharge. The purpose of this study is to determine the relationship between personal hygiene behavior and the incidence of vaginal discharge in adolescent girls at SMA Negeri 1 Godean.Method: This study is a type of quantitative research with a cross sectional approach. The sampling technique in this study is a purposive sampling method with a sample of 60 respondents. The instrument in this study is using a questionnaire. The analysis of greeting data in this study uses chi square. Results: The results of the analysis with the chi square test obtained the results of bivariate analysis found that there was a relationship between personal hygiene behavior and the incidence of vaginal discharge, the value of pvalue=0.002 (pvalue=0.05). Conclusion: The conclusion of this study is that there is a relationship between personal hygiene behavior and the incidence of vaginal discharge in adolescent girls at SMA Negeri 1 Godean Yogyakarta in 2024.